PWE-282 The role of α-fetoprotein in hepatocellular carcinoma surveillance. (28th May 2012) - Jenks, S; Hey, S; Gibson, L; Sturgeon, C; Hayes, P; Bird, T
Abstract : Introduction: The most efficient and cost-effective programme for HCC surveillance is the subject of ongoing debate. Current UK standard practice for HCC surveillance in high risk populations consists of 6 monthly ultrasound (US) and α-fetoprotein (AFP) measurement. However, the most recent international guidelines on HCC surveillance (AASLD) state that US alone is the most appropriate means of HCC surveillance. 1 2 To investigate the relative contributions of US and AFP to HCC surveillance we have performed a retrospective analysis of the records of consecutive cases of newly diagnosed HCC within two patient cohorts. Methods: We retrospectively reviewed the electronic records of: (1) All 78 patients diagnosed with HCC in NHS Lothian between 1 January 2010 and 30 September 2011. (2) All 46 patients referred to the Scottish Liver Transplant Unit (SLTU) with HCC for liver transplant assessment from 1 January 2010 to 31 August 2011. Demographic details, mode of HCC detection and patient outcomes were recorded. Patients were identified as undergoing HCC surveillance if they were having 6 monthly US and AFP measurements. An elevated AFP was defined as >6 kU/l. Results: 36% (28/78) of the patients diagnosed with HCC in NHS Lothian were diagnosed through HCC surveillance. Of these 28 patients 39% (11/28) had the suspicion of HCC raised by AFP alone, 32% (9/28) were detected by both AFP and US and only 25% (7/28) were detected by US alone. 1 HCC was detected by CT scan. The overall sensitivity of AFP for detecting HCC in the surveillance group was 71% (20/28). 84% (36/43) of the SLTU cohort were diagnosed through regular HCC surveillance. 33% (12/36) by AFP alone, 25% (9/36) by US alone and 42% (15/36) by both AFP and US. 69% (25/36) had a raised AFP at HCC diagnosis. 76% (19/25) of patients with a raised AFP at diagnosis were offered potentially curative treatment. Conclusion: In conclusion our data does not support the current AASLD guidelines stating US alone should be used for HCC surveillance. In both patient cohorts over a third of HCC cases detected through surveillance were identified by a rising AFP alone. Our results indicate AFP is therefore an important and effective addition to US. Additional refinement of how AFP levels are interpreted, in particular progressive rises in AFP, may enable increased sensitivity and specificity and further improve the efficacy of HCC surveillance. Competing interests: None declared. References: 1. Bruix J, Sherman M. Management of Hepatocellular Carcinoma: An Update . 2010. http://www.aasld.org/practiceguidelines/ (accessed Feb 2011). 2. Marrero Jorge A, El-Serag Hashem B. Alpha-fetoprotein should be included in the hepatocellular carcinoma surveillance guidelines of the american association for the study of liver diseases. Hepatology 2011;53 :1060–1.